2016
DOI: 10.1080/17470919.2016.1197853
|View full text |Cite
|
Sign up to set email alerts
|

Action priming with biomechanically possible and impossible grasps: ERP evidence from 6-month-old infants

Abstract: Coding the direction of others' gestures is a fundamental human ability, since it allows the observer to attend and react to sources of potential interest in the environment. Shifts of attention triggered by action observation have been reported to occur early in infancy. Yet, the neurophysiological underpinnings of such action priming and the properties of gestures that might be crucial for it remain unknown. Here, we addressed these issues by recording electroencephalographic activity (EEG) from 6-month-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 30 publications
2
11
1
Order By: Relevance
“…Studies carried out with this paradigm have revealed that the temporoparietal component N290 is sensitive to congruency relations starting from 9 months of age (Senju et al, ). Similar results were found in 6‐month‐old infants, using a cueing paradigm where the target presentation was preceded by the presentation of a dynamic possible or impossible hand gesture (Natale et al, ). Results indicate that the N290 component is modulated by congruency relations between cue and target but only when the cue represents a possible hand gesture and not when the cue represents an impossible hand gesture.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…Studies carried out with this paradigm have revealed that the temporoparietal component N290 is sensitive to congruency relations starting from 9 months of age (Senju et al, ). Similar results were found in 6‐month‐old infants, using a cueing paradigm where the target presentation was preceded by the presentation of a dynamic possible or impossible hand gesture (Natale et al, ). Results indicate that the N290 component is modulated by congruency relations between cue and target but only when the cue represents a possible hand gesture and not when the cue represents an impossible hand gesture.…”
Section: Introductionsupporting
confidence: 78%
“…A cueing paradigm was employed (Natale et al, ; Posner, ). As shown in Figure , each trial began with a visually animated but silent fixation point, (i.e., attention getter) randomly selected among 16 different animations, displayed at the center of the screen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between the two experiments at the early processing stages -as indexed by the P1 and N290 components -speaks against one common process. Though both the P1 38 and the N290 37,39 have been found in studies on infants' attention, in our study the stimuli between the two experiments are matched pixel by pixel but differ in their psychological meaning: human (upright) faces are special stimuli from at least birth 3,40 . Our results suggest that the P1 and N290 are neural correlates of different processes, rather than just different aspects of the same (attentional) process, with the N290 being a well-studied correlate of face perception in infants.…”
Section: Discussionmentioning
confidence: 78%